GAYA HIDUP DENGAN KEJADIAN HIPERTENSI DI WILAYAH PEGUNUNGAN DAN PESISIR KABUPATEN BULUKUMBA - Muriyati; Safruddin (Lembaga Penelitian dan Pengabdian Masyarakat (Stikes Panrita Husada Bulukumba), 2018)
Hypertension is an increase in systolic blood pressure of at least 140 mmHg while the diastolic pressure is at least 90 mmHg. The incidence of hypertension in the mountainous and coastal areas of Bulukumba Regency increased from year to year, because it was influenced by unhealthy lifestyles, there were several things that led to hypertension, namely smoking, consumption of alcoholic beverages and habits of fast food, coconut milk and fatty foods. consume high sodium levels. The purpose of this study is to know the relationship between smoking lifestyle, diet, and consumption of alcoholic beverages with the incidence of hypertension. This research method uses analytic design with cross sectional design. The sample in this study were 82 people taken by the Probability Random Sampling method with Cluster Sampling technique. Data analysis in this study uses two tests, namely chi square test and fhiser alternative with a significant level of a (<0.05). The results of this study indicate that smoking is obtained (p = 0.046) so H0 is rejected and Ha is accepted. The pattern of eating is obtained (p = 0.012) then H0 is rejected and Ha is accepted. Consumption of alcoholic beverages obtained value (p = 0.027) then H0 is rejected and Ha is accepted. The conclusion in this study is that the lifestyle is closely related to the incidence of hypertension in the mountainous and coastal regions of Kab. Bulukumba. It is recommended for patients with hypertension to always control blood pressure and maintain or avoid risk factors that can increase blood pressure and maintain a healthy lifestyle.